Long Time Decay Rate to a Bipolar Quantum Drift-Diffusion Model - Yingjie Zhu; Bo Liang; Xiting Peng (Journal of Function Spaces)
This paper is devoted to studying the long time behavior of solutions to a bipolar quantum hydrodynamic in one-dimensional space for general pressure functions. The model is usually applied to simulate some quantum effects in semiconductor devices. The decay rate for time variable is obtained by the entropy functional method and semidiscrete technique.